2013
DOI: 10.1111/btp.12042
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Buffering of Microhabitats is a Critical Factor Mediating Warming Vulnerability of Frogs in the Philippine Biodiversity Hotspot

Abstract: Species may circumvent the impacts of climate warming if the habitats they use reduce ambient temperature. In this study, we identified which frog species from a tropical montane rain forest in the Philippines may be vulnerable to climate warming. To do so, we selected five anuran species that utilize four breeding habitats and identified the sensitivity and exposure of tadpoles and direct‐developer eggs to heat by measuring their critical thermal maximums (CTmax) and the habitat‐specific temperatures they exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 38 publications
(74 reference statements)
2
66
1
Order By: Relevance
“…One iButton logger per plot was hung approximately 1 m above the ground to measure understorey ambient temperature (Scheffers, Brunner et al 2013). To identify the (near-)maximum potential ambient air temperature for our study plots, we hung a second iButton in the upper canopy cover of trees between ten and thirteen meters above the ground (Scheffers, Phillips et al 2013), as close as possible to directly above the understorey ambient logger depending on canopy accessibility.…”
Section: Temperature Datamentioning
confidence: 99%
“…One iButton logger per plot was hung approximately 1 m above the ground to measure understorey ambient temperature (Scheffers, Brunner et al 2013). To identify the (near-)maximum potential ambient air temperature for our study plots, we hung a second iButton in the upper canopy cover of trees between ten and thirteen meters above the ground (Scheffers, Phillips et al 2013), as close as possible to directly above the understorey ambient logger depending on canopy accessibility.…”
Section: Temperature Datamentioning
confidence: 99%
“…Although the depths of some boulder field cavities may exceed 500 cm (personal observation), and no extremely deep temperatures were measured due to the difficulty of deploying sensors amid the complex rock cavity morphology, our data suggested a greater thermal buffering effect would occur in deep cavities. These buffering effects must be taken into consideration when evaluating the vulnerability of species to climate change (Williams et al, 2008) and overlooking these fine-scale effects may overestimate the vulnerability of species to climate change (Luoto and Heikkinen, 2008;Randin et al, 2009;Scheffers et al, 2013). For example, Brereton et al (1995) concluded that the bioclimatic range of B. parvus in Victoria will disappear with only a 1°C rise in mean air temperature.…”
Section: The Thermal Buffering Effect Of Boulder Fields In the Austramentioning
confidence: 99%
“…Understanding acute climate exposure within microhabitats relative to the physiological sensitivities and limits of species that use them is critical in identifying species vulnerability to novel climates (Williams et al ., ; Duarte et al ., ; Scheffers et al ., ). A key research objective is understanding the role habitats will play in moderating the ecophysiological impacts of climate change on ectotherm communities (Huey & Tewksbury, ).…”
Section: Introductionmentioning
confidence: 99%